Analisis Kontrastif Fonologi Bahasa Banjar dan Bahasa Jawa di Desa Sebelimbingan Kecamatan Pulau Laut Utara Kabupaten Kotabaru - Rudy Suryana (STKIP Paris Barantai, 2020)
This study aims to identify the similarities, phonological similarities of Banjar languages and Javanese as a basis for language learning models. The field study was carried out in Sebelimbingan Village, Pulau Laut Utara Subdistrict, Kotabaru Regency, where Banjar and Javanese languages are used by the villagers in everyday language. This research uses descriptive qualitative methods, data collected through observation, and listening and analyzed using synchronous contrastive analysis techniques. The subject of this research is the daily conversation of the Javanese that can be recorded and then carried out a phonological analysis of the Banjar and Javanese phonology in the community of Sebelimbing Village, Pulau Laut Utara District, Kotabaru Regency. Linguistic studies are very interesting to study, especially in contrastive studies of analysis comparing several languages in the world. In phonological studies, especially phonetic studies on equality and similarity in two languages, namely Banjar and Javanese. The comparison of the two languages in the similarity of sound has characteristics in similarities and differences. The results of this study indicate that the similarity between the two languages, namely Banjar language and Javanese language lies at the level of vocabulary, language sounds, and their meanings. At the vocabulary level, there are phonological similarities. This research can be used as a consideration for regional language learning models by utilizing the similarities and similarities held by the two languages, both regarding vocabulary, their meaning and the structure of clauses or sentences. At the very least, the similarity and similarity of the linguistic aspects is used at the beginning of the beginning in learning two languages namely Banjar and Javanese so that they do not experience difficulties in learning and mastering the language. Keywords: Analysis, Contrastive, Phonology, Banjar Language and Javanese Language.